Niche oncogenesis - Scadden, David T. (Henry Stewart Talks, 2014)
The niche hypothesis, The bone marrow niche, Niche targeted therapy, Mesenchymal cells, Dicer1 deletion, Schwachman-Diamond Syndrome, The niche oncongeneis model and clinical applications, Mesenchymal cell dynamics in the body